Disparate individual fates compose robust CD8+ T cell immunity - Buchholz, Veit; Floßdorf, Michael; Hensel, Inge; Kretschmer, Lorenz; Weissbrich, Bianca; Gräf, Patricia; Verschoor, Admar; Schiemann, Matthias; Höfer, Thomas; Busch, Dirk H. (Science, 2013)
Dynamic Protection - During an immune response, CD8+ T cells are recruited to provide protection. Most cells differentiate into short-lived effectors that help to clear the pathogen, whereas others form long-lived memory cells to protect against reinfection. Gerlach et al. (p. 635, published online 14 March) and Buchholz et al. (p. 630, published online 14 March) used in vivo fate mapping of mouse T cells with a defined specificity during a bacterial infection to show that the dynamics of the single-cell response are not uniform. The response of a particular T cell population is the average of a small number of clones that expand greatly (“large clones”) and many clones that only proliferate at low amounts (“small clones”). The memory pool arises largely from small clones whereas effectors are primarily made up of large clones. - A core feature of protective T cell responses to infection is the robust expansion and diversification of naïve antigen-specific T cell populations into short-lived effector and long-lived memory subsets. By means of in vivo fate mapping, we found a striking variability of immune responses derived from individual CD8+ T cells and show that robust acute and recall immunity requires the initial recruitment of multiple precursors. Unbiased mathematical modeling identifies the random integration of multiple differentiation and division events as the driving force behind this variability. Within this probabilistic framework, cell fate is specified along a linear developmental path that progresses from slowly proliferating long-lived to rapidly expanding short-lived subsets. These data provide insights into how complex biological systems implement stochastic processes to guarantee robust outcomes. - The single-cell dynamics as cytotoxic T cells respond to a bacterial infection are analyzed in mice. - The single-cell dynamics as cytotoxic T cells respond to a bacterial infection are analyzed in mice.
Gesehen am 09.12.2020